KONSELING TEMAN SEBAYA (PEER COUNSELING) SUATU INOVASI LAYANAN BIMBINGAN KONSELING DI PERGURUAN TINGGI - Neni Noviza (Wardah, 2011)
The development of students can not be separated from environmental influences, whether physical, psychological, and social. Inherent nature of the environment is changing. Changes in the environment can affect lifestyle (life style) students. If the changes were difficult to predict, or out of range capabilities, then it will give birth to a discontinuity development of individual behavior, such as the occurrence of stagnation (stagnation) development, personal problems or irregularities of behavior. Reality on the ground, not all colleges have a program of guidance and counseling services to help students progress and solve problems for a while this thesis adviser or academic adviser (PA) used as one alternativ in helping students. In some cases students are more open to their peers as compared with the academic supervisor. Mainly for personal and social problems. Closeness, openness and sense of common fate among adolescents may be an opportunity for efforts to facilitate the development of students through peer counseling